2015
DOI: 10.1530/eje-14-0940
|View full text |Cite
|
Sign up to set email alerts
|

No beneficial effects of vitamin D supplementation on muscle function or quality of life in primary hyperparathyroidism: results from a randomized controlled trial

Abstract: Context: Impairments of muscle function and strength in patients with primary hyperparathyroidism (PHPT) are rarely addressed, although decreased muscle function may contribute to increased fracture risk. Objective: We aimed to assess the changes in muscle strength, muscle function, postural stability, quality of life (QoL), and well-being during treatment with vitamin D or placebo before and after parathyroidectomy (PTX) in PHPT patients. Design: A randomized placebo-controlled trial. Patients: We included 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
0
18
0
2
Order By: Relevance
“…Some guidelines advise the use of vitamin D supplements before the operation ( 12 14 ). Recently, several studies analysed the impact of vitamin D correction prior to parathyroidectomy, found that it had an insignificant impact on the outcomes, and suggested that correction of vitamin D deficiency should not delay the operation ( 15 , 16 ). Moreover, theoretically the use of bisphosphonates could reduce the rate of HBS, because they inhibit osteoclasts and reduce bone demineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Some guidelines advise the use of vitamin D supplements before the operation ( 12 14 ). Recently, several studies analysed the impact of vitamin D correction prior to parathyroidectomy, found that it had an insignificant impact on the outcomes, and suggested that correction of vitamin D deficiency should not delay the operation ( 15 , 16 ). Moreover, theoretically the use of bisphosphonates could reduce the rate of HBS, because they inhibit osteoclasts and reduce bone demineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Rolighed and colleagues 167 recently reported the results of a randomized, placebo-controlled study, which investigated whether vitamin D supplementation improved QOL in PHPT. Subjects given 2,800 IU of cholecalciferol for 26 weeks before and 26 weeks following parahyroidectomy demonstrated significant improvements in 25-hydroxyvitamin D levels.…”
Section: Quality Of Lifementioning
confidence: 99%
“…A total of 69 full-text articles were studied for eligibility. Fifteen were found ineligible; nine of these were focused on pharmaceutical agents outside the scope of this review [five vitamin-D supplementation and calcium (12, 7073), two octreotide (10, 11), one hormone replacement therapy (6), one Strontium Ranelate (9)]; two were review articles (74, 75); two had no data on effect of the included drugs (76, 77); one had a main focus other than medical treatment of primary hyperparathyroidism (78); and one was found incomparable to the remaining studies due to incoherent reporting and few subjects (79). Fifty-four articles were thus included in this review.…”
Section: Resultsmentioning
confidence: 99%